KONDISI SOSIAL EKONOMI PENAMBANG BATU DAN PASIR DI KENAGARIAN KOTO BERAPAK KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Sari, Dini Karmila; Rianto, Slamet; Yuherman, Yuherman (STKIP PGRI Sumbar, 2013)
This study aims to obtain data, information and an overview of the socio-economic condition of the rock and sand miners in Kenagarian Koto Berapak views of: 1) education 2) living conditions 3) the level of income 4) health condition. The research method was descriptive. Entire population in the study rocks and sand miners who reside in Kenagarian Koto Berapak Kecamatan Bayang Kabupaten Pesisir Selatan numbering as many as 58 miners, sampling techniques sampling the study was the total number of sample respondents still 58 miners. Research data collection using questionnaires with data analysis using the percentage formula. These results indicate that the indicator 1) the ability of the rock and sand miners families in achieving education in the high school level is quite capable. 2) the ability of the rock and sand miners families in meeting the needs of residence (house) is quite capable. 3) for the income requirement is considered quite capable. 4) the ability of the rock and sand miners families in achieving health needs are considered quite capable. This means that the socio-economic condition of the rock and sand miners in Kenagarian Barapak Koto Berapak Kecamatan Bayang Kabupaten Pesisir Selatan. Belong to prosperous families where the family has been able to meet the overall needs of basic, social, psychological and family development but have not been able to contribute regularly to the public.